Birth preparedness and complication readiness among pregnant women attending antenatal care at the Faculty of Medicine Vajira Hospital, Thailand - Kiataphiwasu N; Kaewkiattikun K (Dove Medical Press, 2018)
Nath Kiataphiwasu, Kasemsis Kaewkiattikun Department of Obstetrics & Gynecology, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, Thailand Background: Maternal and neonatal mortality is a major health problem in developing countries. Birth preparedness and complication readiness (BPCR) is a strategy to encourage pregnant women to make prompt decisions to seek care from skilled birth attendants. Reports of good BPCR vary depending on study setting and population. Most studies of BPCR have been conducted in developing countries, BPCR status and associated factors in Thailand are currently unknown.Objective: To discover the proportion of good BPCR (at least four BPCR indicators), associated factors and predictive factors for good BPCR in pregnant women attending antenatal clinic.Materials and methods: This cross-sectional study was conducted among pregnant women attending the antenatal clinic at the Department of Obstetrics and Gynecology, Faculty of Medicine Vajira Hospital, Thailand, from May 1 to December 31, 2017. The participants were interviewed using the BPCR index developed by the John Hopkins Program for International Education in Gynecology and Obstetrics.Results: Of a total 672 pregnant women, the proportion of good BPCR was 78.6%. The association between baseline characteristics with BPCR status revealed that the good BPCR group was significantly associated with adult pregnancy, married, high education, being employed, high income, extended family, multiparity, first antenatal visit ≤12 weeks and average distance to the hospital >2 hours. Results from multiple logistic regression found that significant predictive factors for good BPCR were a diploma or a bachelor’s degree (ORadj 2.09, 95% CI 1.19–3.69, P=0.010), income more than 10,000 baht (ORadj 2.63, 95% CI 1.37–5.05, P=0.004), extended family (ORadj 2.32, 95% CI 1.41–3.82, P=0.001) and multiparity (ORadj 1.56, 95% CI 1.01–2.42, P=0.047).Conclusion: This study demonstrated that the proportion of good BPCR among pregnant women attending antenatal care was high. Associated factors of good BPCR were adult pregnancy, married status, high education, employed, high income, extended family, multiparity, first antenatal visit at ≤12 weeks and long-distance transportation. Predictive factors for good BPCR were high education, high income, multiparity and extended family. Keywords: birth, birth preparedness, complication readiness, BPCR, maternal mortality, Thailand